Subsystems, communities and networks: articulating ideas and interests in the formulation of public policies - Niedhardt Capella, Ana Claudia [UNESP]; Brasil, Felipe Goncalves (Escola Nacl Adm Publica-enap, 2015)
In the recent literature, the concept of policy subsystem has played a central role in several theoretical models, being considered the prime unit of analysis in approaches of the public policy process. This paper aims to discuss the theoretical construction around the idea of policy subsystems, policy communities and policy networks, as well as to evidence the incorporation and development of these concepts in three theoretical models of policy analysis: the multiple streams model; the punctuated equilibrium framework and the advocacy coalition framework. The theoretical and conceptual debate about the subsystems, communities and policy networks aims to contribute to studies in public policy change processes, especially in perspectives that consider the role of the actors through their ideas, knowledge and interests.
Keywords: public administration; public policies; work group